Analysis of Smart Homestay Business in Karyamukti Village, Cianjur (Case Study on Mrs. Ai's Smart Homestay) - Ryndamayanti, Annisa; Harmadi, Ashur; Misdiyono (Yayasan Sinergi Kawula Muda, 2023)
There are still very few Smart Homestays in the Gunung Padang tourist area and must be refined regarding the technological equipment used. The problem in the object of this research is the accessibility and limitations of human resources in running this business. The purpose of this study was to determine the feasibility of Mrs. Ai's Smart Homestay business in Karyamukti Village using a descriptive analysis method in terms of several aspects including legal aspects, market and marketing aspects, technical and technological aspects, management and HR aspects, financial aspects, economic aspects. And social and environmental aspects. Based on the results of the business feasibility analysis, there are several aspects that are still far from meeting the business feasibility criteria. Business actors are expected to pay more attention to aspects that are still not in accordance with the eligibility criteria so that the business being run can survive and develop much better.